2016
DOI: 10.1128/aac.01867-15
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activity of Ceftaroline against Staphylococcus aureus Isolated in 2012 from Asia-Pacific Countries as Part of the AWARE Surveillance Program

Abstract: b Ceftaroline, the active metabolite of the prodrug ceftaroline-fosamil, is an advanced-generation cephalosporin with activity against methicillin-resistant Staphylococcus aureus (MRSA). This investigation provides in vitro susceptibility data for ceftaroline against 1,971 S. aureus isolates collected in 2012 from seven countries (26 centers) in the Asia-Pacific region as part of the Assessing Worldwide Antimicrobial Resistance and Evaluation (AWARE) program. Broth microdilution as recommended by the CLSI was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 35 publications
(41 reference statements)
0
38
0
1
Order By: Relevance
“…The revised ceftaroline resistance rate against MRSA reported by this study in Asia (1.8%), using version 8.0 of the EUCAST breakpoints, was higher than in other participating regions. Previous studies have identified a set of MRSA isolates collected in Thailand with ceftaroline MIC values of 2 mg/L [12,13,15]. Among the isolates selected for molecular characterization, the majority with ceftaroline MIC values of 2 mg/L had a single amino acid substitution in the non-penicillin-binding domain of penicillin-binding protein 2a (PBP2a), and isolates with ceftaroline MICs of 4 mg/L [13] or 8 mg/L [12,15] all had an additional single amino acid substitution in the penicillin-binding domain of PBP2a.…”
Section: Discussionmentioning
confidence: 99%
“…The revised ceftaroline resistance rate against MRSA reported by this study in Asia (1.8%), using version 8.0 of the EUCAST breakpoints, was higher than in other participating regions. Previous studies have identified a set of MRSA isolates collected in Thailand with ceftaroline MIC values of 2 mg/L [12,13,15]. Among the isolates selected for molecular characterization, the majority with ceftaroline MIC values of 2 mg/L had a single amino acid substitution in the non-penicillin-binding domain of penicillin-binding protein 2a (PBP2a), and isolates with ceftaroline MICs of 4 mg/L [13] or 8 mg/L [12,15] all had an additional single amino acid substitution in the penicillin-binding domain of PBP2a.…”
Section: Discussionmentioning
confidence: 99%
“…Significantly, it is perhaps the drug's most important and distinguishing feature within the class of beta-lactams, its activity against MRSA, that has been met with the most skepticism. In particular, concerns over the appropriateness of the currently recommended dosage of 600 mg twice daily for the treatment of infections caused by S. aureus isolates with MIC values above the current EUCAST breakpoint of 1 mg/liter (14) have been raised, given that CPT MIC 90 values of 2 mg/liter for MRSA have been reported in certain countries within Europe, in Latin America, and in Asia (15)(16)(17)(18)(19)(20). These concerns have driven the initiation of additional clinical trials evaluating an increased frequency of administration (every 8 h) and an extension of the duration of the intravenous infusion of the drug from 1 to 2 h as a potential future mode of administration for infections caused by less susceptible organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is not approved in the United States, the drug has received the qualified infectious disease product designation from the U.S. FDA. Resistance to both of these drugs has been generated in vitro and has been reported clinically and in surveillance studies worldwide, often in association with mutations in mecA (4,(12)(13)(14)(15)(16)(17). We previously reported that passage of a mecA-negative strain of S. aureus, COLnex, passaged in ceftobiprole selected for a highly resistant mutant strain, CRB (4,12,18).…”
mentioning
confidence: 99%